Lessons From the UK's Lockdown: Discourse on Behavioural Science in Times of COVID-19 - Sanders, Jet G.; Tosi, Alessia; Obradovic, Sandra; Miligi, Ilaria; Delaney, Liam (Frontiers in Psychology, 2021)
In recent years behavioural science has quickly become embedded in national level governance. As the contributions of behavioural science to the UK’s COVID-19 response policies in early 2020 became apparent, a debate emerged in the British media about its involvement. This served as a unique opportunity to capture public discourse and representation of behavioural science in this fast-track, high-stake context. Aimed at identifying elements which foster and detract from trust and credibility in emergent scientific contributions to policy making, in Study 1 we use corpus linguistics and network analysis to map the narrative around the key behavioural science actors and concepts which were discussed in the 647 news articles extracted from the 15 most read British newspapers over the 12-week period surrounding the first hard UK lockdown of 2020. We report and discuss 1) the salience of key concepts and actors as the debate unfolded, 2) quantified changes in the polarity of the sentiment expressed toward them and their policy application contexts, and 3) patterns of co-occurrence via network analyses. To establish public discourse surrounding identified themes, in Study 2 we investigate how salience and sentiment of key themes and relations to policy on original Twitter chatter (N = 2,187). In Study 3, we complement these findings with a qualitative analysis of the subset of news articles which contained the most extreme sentiments (N = 111), providing an in-depth perspective of sentiments and discourse developed around keywords, as either promoting or undermining their credibility in, and trust toward behaviourally informed policy. We discuss our findings in light of the integration of behavioural science in national policy making under emergency constraints.